“Yet in His Idle Fire:” Once More unto the Bertram and All’s Well - Clayton, Thomas (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
As a bitter comedy, a dark comedy, and a problem play (all of these so-called), All’s Well has suffered both neglect in the theater for most of its post-creation existence, and vilification from critics for over two centuries, especially in the twentieth. As a result, it is seldom taught and therefore even less often read. More’s the pity, since the real All’s Well is a most entertaining and otherwise rewarding play to experience in the theater and in the study, and far above its traditional status as a disappointment and even “a seedy, seamy affair.” The conventional misreadings center on Bertram, the notorious bed-trick, the ending, and the tonality of the whole. The purpose here is to set these to rights and Helena into perspective as the script seems to present them, and identify this play as a special kind of near-romantic comedy that manages its dramatic vicissitudes so well that All’s Well ends well indeed.